A Tool for measuring organization performance using Ratio Analysis - Adedeji, Elijah Adeyinka Adedeji Adeyinka (Advances in Social Sciences Research Journal, 2014)
Ratio analysis has served as a veritable means of monitoring, measuring and improving performance in an organization. Hence, the study examines a tool for measuring organization performance using ratio analysis. It also ascertains the relevance of internal and external financial reports during ratio analysis for the purpose of establishing key relationships and results in order to appraise financial performance. The study confirmed that there is significant relationship between ratio analysis and organizational performances as well as financial ratios highlight the importance of effective management of an organization. Based on the findings of this study, it was recommended that financial ratios should be computed periodically to reveal areas of strengths and weaknesses, as well as, ratio analysis should be used to measure performance in terms of profitability.